1981
DOI: 10.1128/jb.148.3.782-787.1981
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ribosomal ribonucleic acid synthesis by deoxyribonucleic acid gyrase activity in Escherichia coli

Abstract: The effect of the deoxyribonucleic acid (DNA) gyrase inhibitors coumermycim A1, novobiocin, and oxolinic acid on ribonucleic acid (RNA) synthesis in Escherichia coli was studied in vivo and in vitro. Preferential inhibition of ribosomal RNA (rRNA) synthesis was observed. No effect of oxolinic acid and coumermycim on rRNA synthesis was seen in mutants having a DNA gyrase which is resistant to these inhibitors. In a temperature-sensitive DNA gyrase mutant rRNA synthesis was decreased at nonpermissive temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In E. coli, the G/C-rich OriC end is activated early on commitment of cells to exponential growth [23]. This early activation of the OriC end is associated with the activation of DNA gyrase, which introduces negative supercoils in the DNA [43] and increases the expression of supercoiling-dependent strong transcription units (transcriptons) encoding ribosomal RNA (rrn) and protein genes, as well as of the RpoZ (ω) subunit of RNA polymerase (RNAP), which stabilizes the vegetative (σ 70 ) holoenzyme assembly [44][45][46] and the activator of rrn transcription FIS [46][47][48][49][50][51][52][53][54][55], among other genes involved in boosting growth. Activation of these strong transcriptons requires high negative superhelicity, supplied on the one hand by DNA gyrase, demonstrating a decreasing gradient of binding sites from OriC to Ter [19,21] and on the other hand, by increased production of negative supercoils in the wake of both the translocating replisomes and numerous RNAP molecules engaged in the transcription of stable RNA operons, all of which are oriented towards the Ter [56][57][58].…”
Section: Model Of Regulation Of Gene Expression During the E Coli Grmentioning
confidence: 99%
“…In E. coli, the G/C-rich OriC end is activated early on commitment of cells to exponential growth [23]. This early activation of the OriC end is associated with the activation of DNA gyrase, which introduces negative supercoils in the DNA [43] and increases the expression of supercoiling-dependent strong transcription units (transcriptons) encoding ribosomal RNA (rrn) and protein genes, as well as of the RpoZ (ω) subunit of RNA polymerase (RNAP), which stabilizes the vegetative (σ 70 ) holoenzyme assembly [44][45][46] and the activator of rrn transcription FIS [46][47][48][49][50][51][52][53][54][55], among other genes involved in boosting growth. Activation of these strong transcriptons requires high negative superhelicity, supplied on the one hand by DNA gyrase, demonstrating a decreasing gradient of binding sites from OriC to Ter [19,21] and on the other hand, by increased production of negative supercoils in the wake of both the translocating replisomes and numerous RNAP molecules engaged in the transcription of stable RNA operons, all of which are oriented towards the Ter [56][57][58].…”
Section: Model Of Regulation Of Gene Expression During the E Coli Grmentioning
confidence: 99%
“…While available information concerning the nature of the DNA in the bacterial nucleoid strongly suggests that DNA supercoiling could play a key role in controlling gene expression, data unambiguously demonstrating such a role for supercoiling in vivo are elusive. Results from early experiments with gyrase inhibitors suggested a correlation between sensitivity to catabolite repression and sensitivity to changes in DNA supercoiling (46,47), and genetic studies and work with DNA gyrase inhibitors showed that transcription of rRNA operons is negatively affected by decreases in DNA supercoiling (39). More recently, a survey of 67 random Mu dl-8 Lac' fusions in Salmonella typhimurium showed that most responded to treatment with the DNA gyrase inhibitor coumermycin A1, presumably because of changes in the intracellular DNA supercoiling level (27).…”
Section: Gene Regulation By Dna Supercoilingmentioning
confidence: 99%
“…One important function of FIS is the activation of stable RNA (rRNA and tRNA) and related promoters on nutritional shift-up (Nilsson et al, 1990;Newlands et al, 1992;Champagne and Lapointe, 1998), with subsequent increase in the capacity of the translational machinery. The stable RNA promoters also respond strongly to alterations in negative supercoiling of DNA (Oostra et al, 1981;Lamond, 1985;Ohlsen and Gralla, 1992;Bowater et al, 1994;Free and Dorman, 1994).…”
Section: Introductionmentioning
confidence: 99%